Emerging market economies amid Covid-19: a country-level analysis - Kazi, Noora Naher (2021)
The black swan event COVID-19 has led to 29.5 million confirmed cases and 933,000 deaths globally. Government rules like lockdown, travel restrictions, quarantine and social distancing has led to huge losses in all industries and layoffs. The pandemic has led to the worst global financial collapse and recession so far. The paper focuses on the stock market response of 31 emerging market economies to the COVID-19 pandemic at different stages starting from the declaration of the global pandemic to the announcement of lockdown and its different stages. The side-effect of the interdependent nature of global financial markets are visible as the COVID-19 outbreak shifts from an epidemic to a pandemic. To do a country-level analysis of the impact of the pandemic, stock market returns were chosen as a proxy. Using panel data method, the results show how the stock market returns in five regions responded to COVID-19. The country level results differ from one country to another. The results show the daily confirmed cases and daily deaths had negative impact on stock market returns in the Middle east and European region.